2015
DOI: 10.1016/j.sbspro.2015.01.505
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ Attitudes toward the Use of e-portfolios in Speaking Classes in English Language Teaching and Learning

Abstract: E-portfolios have been used in English language teaching (ELT) to assess and improve writing skills. They can also be used to assess and improve speaking skills. Though the attitudes of students toward the use of e-portfolios in speaking classes are known to be positive, teachers' attitudes toward this method is unknown. Therefore, this study aims to find out the attitudes and perceptions of teachers toward implementing the use of e-portfolios in speaking classes. As it is a small-scale qualitative study, semi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
24
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 16 publications
(50 reference statements)
3
24
0
1
Order By: Relevance
“…Furthermore, several studies found significant positive relationships between perception of teachers and their computer use level (Kobak & Taskin;2012;Korumaz & Karabiyik, 2014;Hüseyin, 2014;Yastibas & Cepik, 2015;Yungwei & Lee, 2015;Rafieea & Purfallah, 2014;Kavanoz Yüksel, & Ozcan, 2015). The successful results of the uses of technology in the education sector have recently encouraged decision makers and educators to allocate more budget to introduce and utilize sophisticated devices to improve learning outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, several studies found significant positive relationships between perception of teachers and their computer use level (Kobak & Taskin;2012;Korumaz & Karabiyik, 2014;Hüseyin, 2014;Yastibas & Cepik, 2015;Yungwei & Lee, 2015;Rafieea & Purfallah, 2014;Kavanoz Yüksel, & Ozcan, 2015). The successful results of the uses of technology in the education sector have recently encouraged decision makers and educators to allocate more budget to introduce and utilize sophisticated devices to improve learning outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, ePortfolios are commonly used in English language teaching (ELT) courses, as a part of writing skills assessment; recently, the possibility of incorporating ePortoflios into speaking courses has also been explored (Yastibas & Cepik, 2015;. Other applications are noted in performing arts education, such as history of music classes (Dunbar-Hall, Rowley, Brooks, Cotton, & Lill, 2015), health sciences (Endacott et al, 2004;McCready, 2007), or foreign language education (Tanaka, Yonesaka, & Ueno, 2015).…”
Section: Applications Of Eportfolio In Learningmentioning
confidence: 99%
“…Many students recognize that ePortfolios allow them to determine where they stand in terms of their career goals and to check how much they have learned about some new process (Yastibas & Cepik, 2015). Others reported an improvement in decision-making, goal-setting, and planning skills (Ambrose et al, 2014).…”
Section: Applications Of Eportfolio In Learningmentioning
confidence: 99%
See 2 more Smart Citations